COMMUNITY WEBSITE DESIGNING PHYSICS USING PHP, MACROMEDIA DREAMWEAVER MX 2004 AND MYSQL - Abrar Nasbey; Rahayu Noveandini, Skom, MM (Jurnal Sistem Informasi, 2007)
Physics is the subject that is no stranger among secondary school students. See howthis develops, less enthused by physics students, because it was considered lessinteresting and boring. For that the author intends to introduce physics via a WebSite.Where, those students who are able to search for Surfer and obtain various types ofinformation related to Physics and Physics can join the Community in order tointeract between members of the community Physics.